Hospital admissions in the Hunter Region from trees and other falling objects, 2008-2012 - Raoul A. Walsh; Lara Ryan (Elsevier, 2017)
Abstract Objective: To assess the impact on hospital admissions produced by trees and other falling objects, to examine these accidents' circumstances, and to investigate the degree of support provided by the data for tree‐related accident prevention. Methods: Admissions to emergency departments in the Hunter Region for the period 2008-2012 allocated the International Classification of Disease 10 code W20 (struck by falling object) were analysed. Results: Of 620 admissions, 125 files were incorrectly coded leaving an eligible sample of 495 W20 admissions. Males made up 79.4% of admissions. Where recorded, the commonest accident locations were workplaces (63.2%) and homes (31.5%). Trees/branches caused only 24 (4.8%) of such accidents with an age‐adjusted admission rate of 0.28 per 10,000 people compared with 6.84 per 10,000 for all falling objects combined. Most tree‐related admissions (at least 62.5%) occurred to persons actively interacting with the tree. Being male (p=0.04) and living in an outer regional area (p=0.001) increased the incidence of tree injuries. Conclusions: Hospital admissions caused by falling objects especially trees are uncommon. Implications for public health: It is difficult to justify any major health promotion expenditure to reduce tree‐related accidents, given their especial rarity. Any funds allocated should focus on preventing falling object injuries in workplaces and homes.